The Effect of Internal Control and Budget Management Compliance on Fraud Detection (Empirical Study at The West Java High Prosecutor's Office In 2024) - Mutiara Ramadhany, Salshafira; Yessie, Afly (Eduvest - Journal of Universal Studies, 2025)
This research aims to examine the effects of internal control and budget management compliance on the detection of fraud. The study focuses on the West Java High Prosecutor’s Office and employs a quantitative approach, using a questionnaire distributed to auditors and treasurers working at the office. The population of the study consisted of 35 auditors and 55 treasurers, with a total of 90 questionnaires distributed and all returned. Data analysis was conducted using multiple linear regression and moderated regression analysis, along with the absolute difference test, utilizing SPSS software. The findings indicate that both internal control and budget management compliance significantly influence the detection of fraud. Specifically, the research shows that stronger internal control systems and greater budget management compliance enhance the ability to detect fraudulent activities. These results highlight the importance of robust internal controls and compliance mechanisms in reducing fraud risks. The study recommends further investigation into the effectiveness of specific internal control mechanisms and their roles in preventing fraudulent behavior, as well as exploring the impact of enhanced budget management practices on fraud detection in other governmental institutions.